NK cells in childhood obesity are activated, metabolically stressed, and functionally deficient - O'BRIEN, EOIN; LITTLE, MARK; FINLAY, DAVID; Tobin, Laura M.; Mavinkurve, Meenal; Carolan, Eirin; Kinlen, David; Cody, Declan; Hogan, Andrew E.; O'Shea, Donal (My University, 2017)
Childhood obesity is a major global concern, with over 50 million children now classified as obese. Obesity has been linked to the development of numerous chronic inflammatory diseases, including type 2 diabetes and multiple cancers. NK cells are a subset of innate effector cells, which play an important role in the regulation of adipose tissue and antitumor immunity. NK cells can spontaneously kill transformed cells and coordinate subsequent immune responses through their production of cytokines. We investigated the effect of obesity on NK cells in a cohort of obese children, compared to children with a healthy weight. We demonstrated a reduction in peripheral NK cell frequencies in childhood obesity and inverse correlations with body mass index and insulin resistance. Compared with NK cells from children with normal weight, we show increased NK cell activation and metabolism in obese children (PD-1, mTOR activation, ECAR, and mitochondrial ROS), along with a reduced capacity to respond to stimulus, ultimately leading to loss of function (proliferation and tumor lysis). Collectively we show that NK cells from obese children are activated, metabolically stressed, and losing the ability to perform their basic duties. Paired with the reduction in NK cell frequencies in childhood obesity, this suggests that the negative effect on antitumor immunity is present early in the life course of obesity and certainly many years before the development of overt malignancies.
PUBLISHED
Keywords: Immunology; Metabolism; Childhood obesity; NK cells; Immunology, Inflammation & Infection; Immunometabolism; NATURAL KILLER CELL